Readiness Analysis of Data Analytics Audit Implementation in Inspectorate General of the Ministry of Finance: An Indonesian Case - Alvan Chaqiqi; Agung Nugroho (The Indonesian Journal of Accounting Research, 2021)
Organizations including public sector organizations are required to utilize data optimally. Unfortunately, only 9% of organizations in the world use data analytics properly (Meulen and McCall, 2018). The Ministry of Finance has a lot of potential data and is the only internal control organization in Indonesia that has initiated the audit data analytics scheme on the roadmap in 2019. This study aims to measure the readiness of audit data analytics implementation reviewed from general to specific. To achieve this objective, this study conducted using qualitative method where the informants were selected based on purposive sampling involving 20 speakers consisted of auditor, supporting unit, auditee, and expert. This study use main model from Gürdür et al. (2019) based on the synthesis of the research study of Schuh et al. (2017) about Industry 4.0 Maturity Index. Then, this model has been elaborated to generate 4 categories, 8 aspects, and 15 criteria. These categories consist of resources readiness, information system readiness, culture readiness, and organizational readiness. The results show that [1] Generally, Ministry of Finance Inspectorate General has resources readiness at high level and other categories at medium level. [2] Specifically, based on two biggest process in Inspectorate General, namely tax audit and financial statement review, show that tax audit have a high level of resource readiness, and the others at a medium level, meanwhile the financial statement review has a high level of resources readiness and information system readiness, and the others at a medium level. [3] Gaps are caused by challenges both from internal and external organization.